用于气体抽取控制的系统和方法 (2018)
本发明涉及向被包括在涡轮增压发动机中的曲轴箱通风系统、排放控制系统和排气再循环(EGR)系统中的个或多个提供真空的系统和方法。在个示例方案中，方法包括从位于压缩机前节气门下游和进气节气门上游的发动机的进气中的真空源吸取真空，以及将所吸取的真空施加于单向曲轴箱通风系统的排出口，其中曲轴箱通风系统的入口被联接到压缩机前节气门上游的发动机进气。 Systems and methods for providing vacuum to one or more of a crankcase ventilation system, an emission control system, and an exhaust gas recirculation (EGR) system included in a turbocharged engine system are provided. In one example, approach, a method includes drawing vacuum from a vacuum source located in an intake of the engine downstream of a pre-compressor throttle and upstream of an intake throttle, and applying the drawn vacuum to a discharge outlet of a uni-directional crankcase ventilation system, where an inlet of the crankcase ventilation system is coupled to the intake of the engine upstream of the pre-compressor throttle.